Immunoassay of Glomalin by Quartz Crystal Microbalance Biosensor Containing Iron Oxide Nanoparticles - Pohanka, Miroslav; Vlcek, Vitezslav (International journal of analytical chemistry, 2020)
Glomalin is a soil protein resembling heat shock protein (HSP) 60 and exerting high affinity to metals, causing retention of water in the environment and improving mechanical stability of soil. Currently, glomalin is determined in the soil or other samples by combination of autoclaving extraction and total protein determination typically by the Bradford method. In this paper, a piezoelectric biosensor was prepared to determine glomalin in a label-free measurement. The biosensor contained antibodies immobilized on quartz crystal microbalance (QCM), and the recognition layer was stabilized by iron oxide nanoparticles. The assay was tested on real soil samples and compared with the standard Bradford assay. Limit of detection of the assay was equal to 2.4 µg/g for a soil extract with a volume of 50 µl. The assay takes approximately half of an hour and was fully correlated to the Bradford assay. The biosensor had significant advantages than the other methods: it worked in a label-free mode and was fully applicable for practical samples.